CFTR inhibitors - Verkman, Alan S; Synder, David; Tradtrantip, Lukmanee; Thiagarajah, Jay R; Anderson, Marc O (Current pharmaceutical design, 2013)
The cystic fibrosis transmembrane conductance regulator (CFTR) protein is a cAMP-regulated Cl- channel whose major function is to facilitate epithelial fluid secretion. Loss-of-function mutations in CFTR cause the genetic disease cystic fibrosis. CFTR is required for transepithelial fluid transport in certain secretory diarrheas, such as cholera, and for cyst expansion in autosomal dominant polycystic kidney disease. High-throughput screening has yielded CFTR inhibitors of the thiazolidinone, glycine hydrazide and quinoxalinedione chemical classes. The glycine hydrazides target the extracellular CFTR pore, whereas the thiazolidinones and quinoxalinediones act at the cytoplasmic surface. These inhibitors have been widely used in cystic fibrosis research to study CFTR function at the cell and organ levels. The most potent CFTR inhibitor has IC50 of approximately 4 nM. Studies in animal models support the development of CFTR inhibitors for antisecretory therapy of enterotoxin-mediated diarrheas and polycystic kidney disease.